Analysis of the effect of providing financial and non-financial compensation on employee job satisfaction studies on employees of the division of human resources (HR), administration and finance of PT. Hanazono Engineering Indonesia - Ahdal Fitriah (Indonesia Auditing Research Journal, 2022)
To win the competition in the business world, entrepreneurs must compete with one another in improving their competitive advantage. The key to winning this competition can be done by increasing the standards and quality of human resources that are owned by the firm. To the quality of human resources, the company must take into account the needs of employees with the best. One way of compensation related to both financial compensation and non-financial compensation for the employees to achieve the level of job satisfaction they expect and employees will feel comfortable with the job in which they live. To determine the relationship between financial compensation and non-financial compensation to employee job satisfaction in this study using a statistical calculation using multiple regression analysis. Multiple regression analysis was used to measure the influence of financial compensation (X1) and non-financial compensation (X2) which is the independent variable employee job satisfaction (Y) which is the dependent variable. This calculation is done to see how that will occur in which the relationship between these variables partially or simultaneously. The formula used in this regression is Y = a+ b1 X1 + b2 X2, where (Y) as job satisfaction, (a) as a constant, (b1 X1) as financial compensation, and (b2 X2) as non-financial compensation. T results will be compared with the t table to determine whether the independent variables have a significant relationship has no significant effect on the dependent variable. The results of multiple regression analysis is Y = 1.417 + 0.549 + 0.549 X1 +0.001 X2.